2016
DOI: 10.1002/ijc.30013
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins, lipids and risk of cancer

Abstract: The epidemiological evidence for an obesity-cancer association is solid, whereas the association between obesity-associated lipoprotein levels and cancer is less evident. We investigated circulating levels of Apolipoprotein A1 (ApoA1), Apolipoprotein B (ApoB), LDL-cholesterol (LDL-C) and HDL-cholesterol (HDL-C) and association to risk of overall cancer and common cancer forms. The Malm€ o Diet and Cancer Study, a population-based prospective cohort study, enrolled 17,035 women and 11,063 men (1991)(1992)(1993)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 47 publications
(92 reference statements)
7
154
1
1
Order By: Relevance
“…However, studies have shown a directly proportional relationship between ApoA‐1 levels and BC risk in women who did not undergo hormone‐replacement therapy . In addition, the ratio of apolipoprotein B (ApoB)/ApoA‐1 was found to be directly associated with BC risk . More research is clearly needed to establish a clear link between Apo‐A1 levels and BC.…”
Section: Rationale For Targeting Cholesterol For Treatment Of Cancermentioning
confidence: 99%
“…However, studies have shown a directly proportional relationship between ApoA‐1 levels and BC risk in women who did not undergo hormone‐replacement therapy . In addition, the ratio of apolipoprotein B (ApoB)/ApoA‐1 was found to be directly associated with BC risk . More research is clearly needed to establish a clear link between Apo‐A1 levels and BC.…”
Section: Rationale For Targeting Cholesterol For Treatment Of Cancermentioning
confidence: 99%
“…Low levels of high-density lipoprotein cholesterol (HDLc) have been associated with breast cancer risk234. However, the relationship between apolipoprotein (apo) A-I levels and breast cancer risk is not clear, as results of published studies are contradictory56.…”
mentioning
confidence: 99%
“…Five prospective cohort studies comprising 487 035 women and at least 15 163 cases were included in the review. A subset of 59 541 participants had LDL and apoB measured at baseline (Table ).…”
Section: Search Strategymentioning
confidence: 99%
“…For the secondary question, all studies evaluated LDL and apoB levels to compare BC risk as follows: Quartiles or cut‐off values Quartiles only Highest vs . lowest levels of exposure (dichotomized according to medical cut‐offs) …”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation